PENGARUH PEMBAGIAN PEKERJAAN DAN BIROKRASI TERHADAP KEPUASAN KERJA PEGAWAI RSUD (SURVEY PADA RUMAH SAKIT UMUM DAERAH KABUPATEN CIREBON, KOTA CIREBON, KABUPATEN INDRAMAYU,DAN KABUPATEN KUNINGAN) - Heriyono Heriyono (Eqien - Jurnal Ekonomi dan Bisnis, 2021)
The background of this research is based on the phenomenon that the Regional Government-owned Regional Hospital, the focus is to serve the community in the health sector, so that pursuing profit is not a top priority for the RSUD, as a result sometimes service is slow, facilities, and administration are also slow. This study aims to analyze the effect of Job Distribution, and Bureaucracy on Employee for the performance of Regional General Hospital staff, either simultaneously or partially. This study explains the causal (cause-effect) relationship between variables and tests the research hypothesis. The technique of determining the data is done by using probability sampling technique. The analysis method uses SEM (Structure Equation Modeling). The results showed that there was a significant effect of Job Distribution, and Bureaucracy on employee job satisfaction by 62.53%. There is a positive and significant influence, either directly or indirectly from the distribution of jobs on employee job satisfaction (23.02%), and bureaucracy on employee job satisfaction (39,51). %),